A Survey of Knowledge Level of Fitness Members in Consuming Muscle-building Supplements in Semarang - Arhab, Abiyyu Bari; Bangsa, Yohanes de la Cruz Gilang Putra (Universitas Negeri Semarang, 2022)
The consumption of supplements to increase muscle mass is considered a necessity for some fitness members. However, there is lack studies which evaluate the level of fitness members’ knowledge about supplements. This research is a type of quantitative descriptive research. 15% of the sample has very good knowledge (very knowledgeable), and 45% of the sample has sufficient knowledge (knowing), unfortunately there are still many respondents (consumers) as much as 40% do not know about the supplements they are taking. Researcher conclude the knowledge levels of fitness member in supplement consumption is still low, and we assume that the factor of education level had a significant effect on the knowledge level of fitness members in consuming supplements.